The History Of Judicial And Prosecutorial Institutions In The Republic Of Uzbekistan (Eurasian Journal of Engineering and Technology, 2026)
The judicial and prosecutorial systems of Uzbekistan have evolved through distinct historical phases: pre-Soviet traditional justice rooted in Islamic shariah and customary law, the centralized Soviet socialist model (1924–1991), early post-independence continuity with limited reforms (1991–2016), and radical modernization since 2017 under President Shavkat Mirziyoyev. This article traces these developments, highlighting the shift from executive-dominated structures to a more independent judiciary aligned with democratic principles, rule of law, and international standards. It examines key legislative milestones, institutional changes, and ongoing challenges, drawing on constitutional, historical, and legal sources.